Evaluation of Simulations for Short-Term Voltage Stability Assessment with Respect to Model Uncertainties - Dorothee Nitsch; Hendrik Vennegeerts (Eng)
In order to evaluate the short-term voltage stability of an electrical power grid, it is necessary to employ not only systematic and well-targeted fault simulations, but also an evaluation method that assesses the criticality of the individual scenarios. A binary decision between stable or unstable, or whether a threshold value is exceeded or not, is inadequate, particularly in instances where the modeling of the system is subject to a certain degree of uncertainty. Since systematic deviations are subject to natural principles and an intervention limit can thus be determined deterministically, an evaluation method is therefore required that allows a statement to be made about the proximity to instability or to a threshold value. It is common practice to employ indices for the evaluation of voltage recovery following a fault event in simulations or from real measurements. However, depending on the specific question being analyzed, the requirements for an index may vary. A review of the literature revealed the existence of several indices that have been developed and applied in the context of various problems and analyses. These indices have been shown to be effective in the respective contexts. However, none of them fully satisfy the requisite criteria for addressing the aforementioned issue. This paper presents and discusses a new index that was developed explicitly for the problem at hand in dealing with model uncertainties, derived requirements from it, and compared it with existing indices from the literature. The benefits of this novel index in comparison with the established ones were visualized based on a number of indicative simulations. Subsequently, the uncertainties inherent in the load parameterization and their implications on the voltage recovery were presented via Monte Carlo simulations. The evaluations of these effects in terms of the distance from the permissible threshold value were then analyzed using the various indices. All simulations were executed within the framework of the IEEE 39 bus New England system.